MR‐FLIP: a new method that combines a functional lumen imaging probe with anatomical information for spatial compliance assessment of the anal sphincter muscles. (2nd August 2017) - Brusa, T.; Abler, D.; Tutuian, R.; Studer, P.; Fattorini, E.; Gingert, C.; Heverhagen, J. T.; Brügger, L. E.; Büchler, P.
Abstract: Aim: Continence results from a complex interplay between anal canal (AC) muscles and sensorimotor feedback mechanisms. The passive ability of the AC to withstand opening pressure – its compliance – has recently been shown to correlate with continence. A functional lumen imaging probe (FLIP) is used to assess AC compliance, although it provides no anatomical information. Therefore, assessment of the compliance specific anatomical structures has not been possible, and the anatomical position of critical functional zones remains unknown. In addition, the FLIP technique assumes a circular orifice cross‐section, which has not been shown for the AC. To address these shortcomings, a technique combining FLIP with a medical imaging modality is needed. Method: We implemented a new research method (MR‐FLIP) that combines FLIP with MR imaging. Twenty healthy volunteers underwent MR‐FLIP and conventional FLIP assessment. MR‐FLIP was validated by comparison with FLIP results. Anatomical markers were identified, and the cross‐sectional shape of the orifice was investigated. Results: MR‐FLIP provides compliance measurements identical to those obtained by conventional FLIP. Anatomical analysis revealed that the least compliant AC zone was located at the proximal end of the external anal sphincter (EAS). The cross‐sectional shape of the AC was found to deviate only slightly from circularity in healthy volunteers. Conclusion: The proposed method is equivalent to classical FLIP. It establishes for the first time direct mapping between local tissue compliance and anatomical structure, which is key to gaining novel insights into (in)continence. In addition, MR‐FLIP provides a tool for better understanding conventional FLIP measurements in the AC by quantifying its limitations and assumptions.